Fundamental frequency patterning and sentence intonation in two Jutlandic dialects - A first approach - Thorsen, Nina; Jul, Bent (Annual Report of the Institute of Phonetics University of Copenhagen, 1981)
In two Jutland areas (Thy and Århus) the fundamental frequency pattern associated with the succession of a stressed plus unstressed syllables can be described as a HIGH plus LOW or FALLlNG pattern, which is the inverse of the Standard Copenhagen LOW plus HIGH-FALLING one. We suggest that the difference be accounted for in terms of a difference in timing with respect to the peak and troughs of a basically triangular "wave". - Non-statement intonation contours may be rarer in these dialects than in Standard Copenhagen.